Robust Programmable Photonic Circuits Based on a Floquet-Lieb Topological Waveguide Lattice - Hanfa Song; Tyler J. Zimmerling; Vien Van (IEEE Photonics Journal)
We propose a robust programmable photonic integrated circuit platform based on a 2D Floquet-Lieb topological lattice. Reconfigurable topological photonic lattices typically require creating topologically distinct domains to guide interface modes, which requires a large number of coupling elements to be tuned and severely constraints the realizable circuit configurations. Here by taking advantage of the natural hopping sequence of light in the Floquet-Lieb microring lattice, we show that line defect modes and flat-band resonance modes can be excited by tuning only selective coupling elements, thus enabling efficient light steering and localization in the lattice interior. We show how basic circuit elements such as waveguide bends, splitters, combiners, and resonators, can be formed in the lattice, which can be used to construct general photonic integrated circuits. Compared to conventional topologically-trivial waveguide meshes, our topological photonic lattice requires fewer tuning elements while offering better tolerance to defects and random variations due to topological protection. The proposed topological lattice can thus provide an efficient and robust platform for implementing classical and quantum integrated photonic circuits.